Changes in m6A RNA methylation contribute to heart failure progression by modulating translation. (17th December 2019) - Berulava, Tea; Buchholz, Eric; Elerdashvili, Vakhtang; Pena, Tonatiuh; Islam, Md Rezaul; Lbik, Dawid; Mohamed, Belal A.; Renner, Andre; von Lewinski, Dirk; Sacherer, Michael; Bohnsack, Katherine E.; Bohnsack, Markus T.; et al.
ABSTRACT: Aims: Deregulation of epigenetic processes and aberrant gene expression are important mechanisms in heart failure. Here we studied the potential relevance of m6A RNA methylation in heart failure development. Methods and results: We analysed m6A RNA methylation via next‐generation sequencing. We found that approximately one quarter of the transcripts in the healthy mouse and human heart exhibit m6A RNA methylation. During progression to heart failure we observed that changes in m6A RNA methylation exceed changes in gene expression both in mouse and human. RNAs with altered m6A RNA methylation were mainly linked to metabolic and regulatory pathways, while changes in RNA expression level mainly represented changes in structural plasticity. Mechanistically, we could link m6A RNA methylation to altered RNA translation and protein production. Interestingly, differentially methylated but not differentially expressed RNAs showed differential polysomal occupancy, indicating transcription‐independent modulation of translation. Furthermore, mice with a cardiomyocyte restricted knockout of the RNA demethylase Fto exhibited an impaired cardiac function compared to control mice. Conclusions: We could show that m6A landscape is altered in heart hypertrophy and heart failure. m6A RNA methylation changes lead to changes in protein abundance, unconnected to mRNA levels. This uncovers a new transcription‐independent mechanisms of translation regulation. Therefore, our data suggest that modulation of epitranscriptomic processes such as m6A methylation might be an interesting target for therapeutic interventions.